2020
DOI: 10.1038/s41388-020-1195-6
|View full text |Cite
|
Sign up to set email alerts
|

RASSF10 is frequently epigenetically inactivated in kidney cancer and its knockout promotes neoplasia in cancer prone mice

Abstract: Kidney cancer incidences are rising globally, thereby fueling the demand for targeted therapies and precision medicine. In our previous work, we have identified and characterized the Ras-Association Domain Family encoding ten members that are often aberrantly expressed in human cancers. In this study, we created and analyzed the Rassf10 knockout mice. Here we show that Rassf10 haploinsufficiency promotes neoplasia formation in two established mouse cancer models (Rassf1A −/− and p53 −/−). Haploinsufficient Ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“… 25 , 26 Cancers of the kidney are accompanied by a high and rising morbidity across the globe, and there is an urgent sense that improvements must now come from fresh approaches. 27 The current study has provided evidence reporting that miR-27a accelerated angiogenesis of HUVECs by downregulating SFRP1 expression. The high expression of miR-27a has been found to augment sprout formation in endothelial cells and then angiogenesis through stimulating the repulsion of neighboring endothelial cells.…”
Section: Discussionmentioning
confidence: 59%
“… 25 , 26 Cancers of the kidney are accompanied by a high and rising morbidity across the globe, and there is an urgent sense that improvements must now come from fresh approaches. 27 The current study has provided evidence reporting that miR-27a accelerated angiogenesis of HUVECs by downregulating SFRP1 expression. The high expression of miR-27a has been found to augment sprout formation in endothelial cells and then angiogenesis through stimulating the repulsion of neighboring endothelial cells.…”
Section: Discussionmentioning
confidence: 59%
“…To a certain extent, this result also indicated that the immune microenvironment of LUAD is an important factor affecting tumor immunotherapy. Although there are many research reports on screening tumor prognostic markers [ 40 42 ], research on the correlation between these markers and TIICs in the TME of LUAD is scarce. To elucidate the mechanism underlying the functions of CCR2, CCR4, P2RY12, and P2RY13 in immune microenvironment of LUAD, we performed GSEA and correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of promoters in CGIs is the most recognised mechanism of epigenetic alterations in cancer cells and has been well implicated in various cancer types. Abundant TSGs are under hypermethylation, such as RASSF10 in kidney cancer [42], SIX3 in glioblastoma [43], CDKN2A and PTEN in melanoma [44,45], etc. Besides, not only TSGs hypermethylation is commonly seen in many cancers, but additional genes involved in multiple pivotal cellular functions also present hypermethylation.…”
Section: Intratumor Epigenetic Alterationsmentioning
confidence: 99%